Conventional versus modified nipple sparing mastectomy in immediate breast reconstruction: Complications, aesthetic, and patient-reported outcomes - Najmiddinov, Bakhtiyor; Park, Joseph Kyu-hyung; Yoon, Kyung-Hwak; Myung, Yujin; Koh, Hyoung Won; Lee, Ok Hee; Hoon, Jeong Jae; Shin, Hee Chul; Kim, Eun-Kyu; Heo, Chan Yeong (Frontiers in Surgery, 2022)
Background: Nipple-sparing mastectomy (NSM) followed by immediate breast reconstruction (IBR) is the optimal surgical treatment for breast cancer. However, investigations are ongoing to improve the surgical technique to achieve better results. This study aimed to evaluate the outcomes of modified NSM (m-NSM), which preserves the anterior lamellar fat layer, in patients who underwent IBR. Methods: All patients who underwent modified NSM (m-NSM) or conventional NSM (c-NSM) followed by IBR using autologous tissue or implants were retrospectively reviewed between January 2014 and January 2021. Two mastectomy types were compared in terms of postoperative complications and aesthetic outcomes using panel assessment scores by physicians and reported outcomes using Breast-Q. In addition, postoperative evaluations of the thickness of mastectomy flap was performed using CT scan images. Results: A total of 516 patients (580 breasts) with NSM (143 breasts with c-NSM and 437 breasts with m-NSM) followed by IBR were reviewed. The mean±SD flap thickness was 8.48±1.81 mm in patients who underwent m-NSM, while it was 6.32±1.15 mm in the c-NSM cohort (p=0.02). The overall major complications rate was lower in the m-NSM group (3.0% versus 9.0%, p<0.013). Ischemic complications of the mastectomy flap and nipple-areolar complex (NAC) were more in c-NSM, although the difference was not statistically significant. The mean panel assessment scores were higher in the m-NSM group (3.14 (good) and 2.38 (fair) in the m-NSM and c-NSM groups, respectively; p<0.001). Moreover, m-NSM was associated with greater improvements in psychosocial (p<0.001) and sexual (p=0.007) well-being. Conclusions: Preserving the anterior lamellar fat in NSM was associated with thicker mastectomy flap, overall lower rates of complications, including ischemia of the mastectomy flap and nipple-areolar complex, and was associated with better aesthetic outcomes and improved quality of life.